2017
DOI: 10.1016/s2095-3119(16)61468-5
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic rice expressing a novel phytase-lactoferricin fusion gene to improve phosphorus availability and antibacterial activity

Abstract: The developing trends of livestock production are efficiency, safety and sustainability, which face two major challenges: low availability of phytate phosphorus and abuse of antibiotics. As a solution phytases and antimicrobial peptides are applied as feed additives. However, phytases and antimicrobial peptides are susceptible to proteases, costly by fermentation and potential toxic to production hosts. We transformed an optimized phytase-lactoferricin fusion gene PhyLf driven by an endosperm-specific promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Using endosperm-speci c promoter Gt13a and a signal peptide targeting the OsrhGM-CSF to the protein bodies, Ning et al achieved the high expression level of OsrhGM-CSF protein in rice endosperm (Ning et al 2008). Wang et al also reported that a novel phytase-lactoferricin fusion gene driven by endosperm-speci c promoter Gt13aP with its signal peptide sequence Gt13aSP could improve the phosphorus availability and antibacterial activity of rice seeds (Wang et al 2017). However, the loading of exogenous proteins inside the cell is limited, the cell wall may be a good subcellular structure for directed accumulation of exogenous proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Using endosperm-speci c promoter Gt13a and a signal peptide targeting the OsrhGM-CSF to the protein bodies, Ning et al achieved the high expression level of OsrhGM-CSF protein in rice endosperm (Ning et al 2008). Wang et al also reported that a novel phytase-lactoferricin fusion gene driven by endosperm-speci c promoter Gt13aP with its signal peptide sequence Gt13aSP could improve the phosphorus availability and antibacterial activity of rice seeds (Wang et al 2017). However, the loading of exogenous proteins inside the cell is limited, the cell wall may be a good subcellular structure for directed accumulation of exogenous proteins.…”
Section: Discussionmentioning
confidence: 99%